2021
DOI: 10.1186/s43019-021-00098-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost, safety, and rehabilitation of same-stage, bilateral total knee replacements compared to two-stage total knee replacements

Abstract: Background Many patients experience bilateral knee osteoarthritis and require bilateral total knee replacement (TKR). Same-stage, bilateral TKR is proposed to be a cost-effective and safe solution compared to two-stage, but conflicting results in the literature are reported. We aim to compare the costs, safety, and rehabilitation performance of patients in same-stage versus two-stage, bilateral TKR with our centre’s perioperative protocol. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Since many factors influence the surgery outcomes, including patient expectations [9,20,23,24], the patient's mental condition before surgery [23,25,26], as well as the presence of other comorbidities [19,23,27], is also important to record these attributes when evaluating the results. The impact of one-time bilateral knee replacement on functional outcomes in groups, which we did not analyse in our study is questionable [28][29][30][31][32]. Krivanek et al [33] reported that there were no statistically significant differences in functional outcomes in the short-term follow-up between single bilateral and unilateral total knee replacement, although range of movement may be higher in the bilateral group.…”
Section: Discussionmentioning
confidence: 66%
“…Since many factors influence the surgery outcomes, including patient expectations [9,20,23,24], the patient's mental condition before surgery [23,25,26], as well as the presence of other comorbidities [19,23,27], is also important to record these attributes when evaluating the results. The impact of one-time bilateral knee replacement on functional outcomes in groups, which we did not analyse in our study is questionable [28][29][30][31][32]. Krivanek et al [33] reported that there were no statistically significant differences in functional outcomes in the short-term follow-up between single bilateral and unilateral total knee replacement, although range of movement may be higher in the bilateral group.…”
Section: Discussionmentioning
confidence: 66%
“…Simultaneous bilateral arthroplasty of the knee and hip has been documented as a good alternative to staged procedures, 20 , 21 , 22 with benefits including shorter total recovery time, single anesthetic, and significantly reduced overall hospital stay and costs. 20 , 21 , 22 , 23 , 24 Compared to simultaneous bilateral TAR, simultaneous TAR and contralateral AA has the advantages of shorter operation time and low cost. However, this balance also relies on the local reimbursement policy by Medicare.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who underwent bilateral AA were noted to have great difficulty with inclines, stairs, and walking on uneven terrain. Simultaneous bilateral arthroplasty of the knee and hip has been documented as a good alternative to staged procedures, 20–22 with benefits including shorter total recovery time, single anesthetic, and significantly reduced overall hospital stay and costs 20–24 . Compared to simultaneous bilateral TAR, simultaneous TAR and contralateral AA has the advantages of shorter operation time and low cost.…”
Section: Discussionmentioning
confidence: 99%
“…Degenerative arthritis of the knee is characterized by pain and deterioration of knee function in middle-aged and elderly patients, thereby affecting the quality of life. [1,2] With the aging population, the incidence of degenerative arthritis has been increasing, as well as its treatment cost. [3] Various treatment methods are available.…”
Section: Introductionmentioning
confidence: 99%